2014
DOI: 10.1111/1469-0691.12336
|View full text |Cite
|
Sign up to set email alerts
|

KPC-2 and OXA-48 carbapenemase-harbouring Enterobacteriaceae detected in an Austrian wastewater treatment plant

Abstract: Multiresistant Enterobacteriaceae, like carbapenemase-producing strains, have their primary reservoir in medical institutions. They can also be found with increasing tendency in other reservoirs. One possible way for entrance of multiresistant Enterobacteriaceae into the environment is via waste water. The aim of the study was to screen isolates from a wastewater treatment plant for the presence of carbapenemase-producing Enterobacteriaceae. Three isolates harboured carbapenemase genes, one Klebsiella pneumoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 24 publications
4
33
0
1
Order By: Relevance
“…Nevertheless, reports regarding their occurrence in environmental matrices are increasingly frequent [3]. For instance, Klebsiella pneumoniae carbapenemase (KPC)-producing isolates have been recovered from rivers located in France [4], Portugal [5] and Brazil [6] as well as from sewage samples in China [7], Brazil [8] and Austria [9]. Polluted rivers frequently flow to oceans, likely contaminating seawater with MDR bacteria and making these aquatic environments potential vectors of resistance for beach frequenters.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, reports regarding their occurrence in environmental matrices are increasingly frequent [3]. For instance, Klebsiella pneumoniae carbapenemase (KPC)-producing isolates have been recovered from rivers located in France [4], Portugal [5] and Brazil [6] as well as from sewage samples in China [7], Brazil [8] and Austria [9]. Polluted rivers frequently flow to oceans, likely contaminating seawater with MDR bacteria and making these aquatic environments potential vectors of resistance for beach frequenters.…”
Section: Introductionmentioning
confidence: 99%
“…Since its first description in Turkey (27), numerous reports have indicated the spread of OXA-48 type carbapenemase in Mediterranean countries (28)(29)(30), where it represents the most common carbapenemase type (31). Subsequently, several studies have reported the isolation of OXA-48-producing Enterobacteriaceae from different samples (32,33). Prior to its first description in Algeria, Poirel et al suggested that OXA-48 may be endemic in this country (34).…”
mentioning
confidence: 99%
“…Viable isolates of CRBP were recovered from hospital sewage both before and after disinfection (Ferreira et al, 2011;Chagas et al, 2011;Zhang et al, 2013;Chandran et al, 2014). From the mixture of domestic and hospital wastewaters two carbapenem-resistant Klebsiella pneumoniae and one Escherichia coli were recovered (Galler et al, 2014). From municipal sewage in Beijing, 37 isolates of CRBP were isolated (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the numbers of viable CRBP in wastewater remain to be determined, in order to quantify the influence of wastewater on the spread of CRBP in the environment. Moreover, the temperature at which the CRBP 35-37°C (Girlich et al, 2010;Ferreira et al, 2011;Walsh et al, 2011;Galler et al, 2014;Tanner et al, 2015) or was not specified at all (Chagas et al, 2011;Poirel et al, 2012;Picao et al, 2013;Zhang et al, 2013). Cultivation at 37°C allows for the isolation of intrinsically carbapenem-resistant bacteria which are autochthonous populations in environmental samples.…”
Section: Introductionmentioning
confidence: 99%